Law enforcement and academics working together on cold case investigations: lessons learned and paths forward. Issue 2 (25th April 2020) - Fox, Bryanna; Miley, Lauren N.; Allen, Scott; Boness, Jordan; Dodge, Cassandra; Khachatryan, Norair; Lyle, MacKenzie; McKinley, Sean; Peake, Jeff; Rozo, Maria
Abstract : Purpose: The purpose of this study is to outline the specific details and lessons learned during a cold case collaborative effort, which granted graduate students and a professor from the University of South Florida the opportunity to assist Pasco Sheriff's Office in the investigation of a cold case homicide. Methodology: The collaboration between law enforcement and academics is a new and emerging strategy to investigate cold cases and identify the elusive offenders who committed these crimes. Such collaboration aids law enforcement by obtaining a force multiplier for investigative resources, accessing cutting-edge evidence-based research and cultivating innovative approaches to their work. For academics, such collaboration allows the unique opportunity to engage in translational criminology, which is an important and increasingly encouraged aspect of the field. Findings: In this paper, the authors provide an overview of the process used to study this cold case as part of an experiential academic course, provide evidence-based research findings relevant to cold case investigations and outline the steps for others to replicate the efforts. Originality/value: The authors describe in detail the process used to "work" the cold case, academic research that the authors found useful in understanding and investigating cold cases, important lessons learned and advice for future academics and practitioners who undertake an incredible collaborative effort such as this.